2013
DOI: 10.1261/rna.040204.113
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of mRNAs associated with the protein SMN whose depletion decreases their axonal localization

Abstract: Spinal muscular atrophy is a neuromuscular disease resulting from mutations in the SMN1 gene, which encodes the survival motor neuron (SMN) protein. SMN is part of a large complex that is essential for the biogenesis of spliceosomal small nuclear RNPs. SMN also colocalizes with mRNAs in granules that are actively transported in neuronal processes, supporting the hypothesis that SMN is involved in axonal trafficking of mRNPs. Here, we have performed a genome-wide analysis of RNAs present in complexes containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 72 publications
7
59
0
Order By: Relevance
“…These studies suggest an involvement of SMN in the regulation of the assembly of ribonucleoproteins responsible for the transport, stability, and/or local translation of axonal mRNAs (Talbot and Davies 2008;Akten et al 2011;Fallini et al 2011;Hubers et al 2011). Consistent with this hypothesis, we recently identified numerous axonal mRNAs associated with the SMN complex in differentiated NSC-34 motor neuron-like cells using a genome-wide analysis (Rage et al 2013). We found also that axonal localization of some mRNAs is altered in SMN-depleted cells, indicating that SMN deficiency might indeed lead to the mislocalization of mRNPs required for axonal outgrowth and/or function.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…These studies suggest an involvement of SMN in the regulation of the assembly of ribonucleoproteins responsible for the transport, stability, and/or local translation of axonal mRNAs (Talbot and Davies 2008;Akten et al 2011;Fallini et al 2011;Hubers et al 2011). Consistent with this hypothesis, we recently identified numerous axonal mRNAs associated with the SMN complex in differentiated NSC-34 motor neuron-like cells using a genome-wide analysis (Rage et al 2013). We found also that axonal localization of some mRNAs is altered in SMN-depleted cells, indicating that SMN deficiency might indeed lead to the mislocalization of mRNPs required for axonal outgrowth and/or function.…”
Section: Introductionsupporting
confidence: 69%
“…In this work, we examined the transport of the mRNA encoding the mouse Annexin A2 (Anxa2) that we previously showed to be SMN-dependent in differentiated NSC-34 motor neuron-like cells (Rage et al 2013). Annexin A2 is a ubiquitous Ca 2+ -binding protein that is essential for actin-dependent vesicle transport and which has been shown to be a critical regulator of actin remodeling in the proximity of dynamic cellular membranes (Hayes et al 2006;Grieve et al 2012;Gabel et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ALS-causing mutations in the RNA-binding protein TDP-43 impairs axonal trafficking of mRNA granules to distal axons [41]. Similarly, reduced levels of survival of motor neuron (SMN) decrease axonal mRNA localization and human SMN1 mutations that alter the amount of functional protein are responsible for most SMA cases [42]. Reduced SMN levels, such as seen in SMA, cause increase expression of microRNA-138, which, in turn, leads to reduced local mammalian target of rapamycin synthesis and activity in axons [43].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…The studies identified about 400 RNA species potentially binding with axonal SMN. A further study found more than 1000 genes dysregulated in neurites of NSC-34 cells and smn-depleted primary mouse motor neurones [121][122][123]. Among these genes are a number involved in axonal outgrowth, synaptogenesis, neurogenesis and neurotransmitter release [121,122].…”
Section: Accepted Manuscriptmentioning
confidence: 97%